Detection and identification of Xanthomonas oryzae pv. oryzicola using quantitative real-time PCR and digital PCR - ZHANG Jiannan; WANG Yiming; ZHANG Jiejing; CHEN Lei; LUO Jinyan; YI Jianping; LI Bin; AN Qianli (浙江大学学报. 农业与生命科学版)
Bacterial leaf blight of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) and bacterial leaf streak of rice caused by Xanthomonas oryzae pv. oryzicola (Xoc) are two important bacterial diseases of rice. Identification of Xoo and Xoc belonging to the same species is critical for quarantine and control the diseases. Here, we found that the gene fhuE encoding ferric-rhodotorulic acid/ferric-coprogen receptor in Xoo and Xoc became pseudogenes after partial deletion during evolution. We designed Xoc-specific primers XocFhuE-F (5<alternatives>´<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/9EF5767D-901A-4e03-A6D2-DE2B4A8111EB-M005.jpg"/></alternatives>-ATCGAACGATGTCACCAGGG-3<alternatives>´<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/9EF5767D-901A-4e03-A6D2-DE2B4A8111EB-M005.jpg"/></alternatives>) and XocFhuE-R (5<alternatives>´<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/9EF5767D-901A-4e03-A6D2-DE2B4A8111EB-M005.jpg"/></alternatives>-AGAAACGTGCGGCCAGATAA-3<alternatives>´<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/9EF5767D-901A-4e03-A6D2-DE2B4A8111EB-M005.jpg"/></alternatives>) targeting the sequences present in the Xoc fhuE pseudogene but absent in the Xoo fhuE pseudogene. Polymerase chain reaction (PCR) amplification produced only a 159 bp DNA fragment from only Xoc strains using the primers XocFhuE-F/XocFhuE-R. Based on the Xoc-specific primers, we developed SYBR Green quantitative real-time PCR (qPCR) and EvaGreen droplet digital PCR (dPCR) methods to detect and identify Xoc. In a 20 μL reaction system with 1 μL of template, the detection limit of qPCR on Xoc was 1.6×104 CFU/mL in bacterial suspension and 1.2×103 CFU/seed in rice seeds; the detection limit of dPCR on Xoc was 1.6×103 CFU/mL in bacterial suspension and 1.2×102 CFU/seed in rice seeds. In conclusion, SYBR Green qPCR and EvaGreen dPCR based on the Xoc-specific primers XocFhuE-F/XocFhuE-R provide effective methods for quarantine of Xoc and monitoring of the bacterial leaf streak disease of rice.